An Overview of RNA-Based Scaffolds for Osteogenesis - Damiati, Laila A.; El-Messeiry, Sarah (Frontiers in Molecular Biosciences, 2021)
Tissue engineering provides new hope for the combination of cells, scaffolds, and bifactors for bone osteogenesis. This is achieved by mimicking the bone’s natural behavior in recruiting the cell’s molecular machinery for our use. Many researchers have focused on developing an ideal scaffold with specific features, such as good cellular adhesion, cell proliferation, differentiation, host integration, and load bearing. Various types of coating materials (organic and non-organic) have been used to enhance bone osteogenesis. In the last few years, RNA-mediated gene therapy has captured attention as a new tool for bone regeneration. In this review, we discuss the use of RNA molecules in coating and delivery, including messenger RNA (mRNA), RNA interference (RNAi), and long non-coding RNA (lncRNA) on different types of scaffolds (such as polymers, ceramics, and metals) in osteogenesis research. In addition, the effect of using gene-editing tools—particularly CRISPR systems—to guide RNA scaffolds in bone regeneration is also discussed. Given existing knowledge about various RNAs coating/expression may help to understand the process of bone formation on the scaffolds during osseointegration.